ANALISIS VALUE PROPOSITION CANVAS (VPC) TERHADAP KEPUASAN PELANGGAN (STUDI KASUS PADA USAHA OMOCHI.BDG KOTA BANDUNG) - Alcaf, Audy Fitriana; Muttaqin, Ridlwan; Karamang, Ezra (Journal of Information System, Applied, Management, Accounting and Research, 2025)
The purpose of this study is to examine how the Value Proposition Canvas (VPC) and its impact on customer satisfaction at Omochi.bdg, a culinary business in Bandung. The research employs a mixed methods approach by collecting data through questionnaires from customers and in-depth interviews with the owner, staff, and active consumers. The results show that most value proposition elements such as product uniqueness, packaging design, practicality, and accessibility meet client expectations and have a positive effect on satisfaction and loyalty. However, some obstacles remain in terms of service responsiveness, delivery consistency, and product information completeness. Overall, this study confirms that an effective implementation of the Value Proposition Canvas can enhance perceived value and customer satisfaction, and recommends that Omochi.bdg improve digital services, communication, and product innovation to maintain competitiveness and business sustainability.